2003
DOI: 10.1007/s00223-002-1032-7
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Analysis of the Mineralization of Type I Collagen via a Polymer-Induced Liquid-Precursor (PILP) Process

Abstract: We have put forth the hypothesis that collagen is mineralized during bone formation by means of a polymer-induced liquid-precursor (PILP) process, in which a liquid-phase mineral precursor could be drawn into the gaps and grooves of the collagen fibrils by capillary action, and upon solidification, leave the collagenous matrix embedded with nanoscopic crystallites of hydroxyapatite. This hypothesis is based upon our observations of capillarity seen for liquid-phase mineral precursors generated with calcium car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
163
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(174 citation statements)
references
References 41 publications
9
163
0
2
Order By: Relevance
“…32 It was reported that colloidal ACC nanoparticles were generated in the solution by using the ammonium carbonate diffusion method in the presence of highly concentrated acidic polymers and calcium ion. 33 The ACC nanoparticle is an effective vehicle for transportation of CaCO 3 to construct three-dimensional interpenetrated hybrids. 33 In recent years, it is widely recognized that the aggregation-mediated pathway of mineralization is important to understand biomineralization.…”
Section: Formation Of Caco 3 /Chitin-whisker Hybrids Y Yamamoto Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…32 It was reported that colloidal ACC nanoparticles were generated in the solution by using the ammonium carbonate diffusion method in the presence of highly concentrated acidic polymers and calcium ion. 33 The ACC nanoparticle is an effective vehicle for transportation of CaCO 3 to construct three-dimensional interpenetrated hybrids. 33 In recent years, it is widely recognized that the aggregation-mediated pathway of mineralization is important to understand biomineralization.…”
Section: Formation Of Caco 3 /Chitin-whisker Hybrids Y Yamamoto Et Almentioning
confidence: 99%
“…33 The ACC nanoparticle is an effective vehicle for transportation of CaCO 3 to construct three-dimensional interpenetrated hybrids. 33 In recent years, it is widely recognized that the aggregation-mediated pathway of mineralization is important to understand biomineralization. 34,35 It has been proposed that living organisms also use ACC nanoparticles for storage, transportation and mineralization of CaCO 3 in their systems.…”
Section: Formation Of Caco 3 /Chitin-whisker Hybrids Y Yamamoto Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…A special feature of the PILP phases is that they allow easy morphosynthesis of novel, biorelevant mineral structures through the shaping of a liquid on the micrometer scale so that crystallization occurs without requiring mass transport over longer distances. [14,15] Herein we extend this approach to polar organic molecules by studying the formation of PILP phases consisting of charged amino acids and oppositely charged polyelectrolytes in ethanol/water mixtures. While addition of ethanol to an aqueous solution of the pure amino acid leads to well shaped single crystals, stable PILP microdroplets are formed spontaneously by adding an oppositely charged polyelectrolyte to the starting solution.…”
mentioning
confidence: 99%
“…For instance, mineralization of collagen in the presence of poly(acrylic acid) (PAA), a synthetic anionic polymer, leads to a hierarchical composite structure similar to natural bone tissue [37]. The polymer-induced liquid precursor (PILP) phase stabilized by PAA exhibits liquid-like properties and is suggested to be drawn into the gaps within collagen fibrils by capillary effects.…”
Section: Introductionmentioning
confidence: 99%